Lumbar Spinal Stenosis: Multidisciplinary Care Pathway for Radiology, Nursing & Physical Therapy - Mohajer, Ghazy Hassan; Khormi, Amnah Abdu; Safhi, Wael Atiah; Malhan, Ali Majed Mohammed; Matabi, Atheer Ibrahim Hadi; Alsbee, Mansor Ali Ahmad; Almotairi, Mohammed Salem; Alhathiq, Abdulelah Hassan; Rayyani, Abdullah Ahmed; Ogdi, Khaled Mohammed; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Lumbar spinal stenosis (LSS) is a leading cause of pain, gait limitation, and surgery in older adults. Because symptoms reflect both fixed anatomic narrowing and posture-dependent dynamics, single-modality decisions underperform. Aim: To outline a multidisciplinary care pathway integrating radiology, nursing, and physical therapy (PT) to improve diagnostic accuracy, functional outcomes, and value. Methods: Narrative synthesis of core domains—anatomy, etiology, epidemiology, pathophysiology, history/physical, evaluation, treatment, prognosis, complications, patient education, and team operations—emphasizing actionable links between imaging phenotypes (central, lateral recess, foraminal, extraforaminal) and bedside/rehabilitation decisions. Results: Flexion widens canal/foramina; extension worsens crowding—an insight that aligns patient education and PT toward flexion-biased programs. MRI remains first-line; axial-loading MRI and CT/myelography resolve discrepancies or contraindications. Standardized MRI grading (e.g., Schizas/Chen Jia/Lee) plus functional metrics (SPWT, ODI) enable decision-ready reports. Epidural injections provide short-term relief with modest effects on walking; medial branch radiofrequency helps facet-predominant pain. When needed, decompression—open, minimally invasive, or endoscopic—improves pain and function; fusion is reserved for instability/deformity. Interspinous spacers benefit selected extension-sensitive, one-to-two-level disease without osteoporosis/instability. <!–StartFragment–> <span style="font-size: 11.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: Aptos; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Conclusion:<span style="font-size: 11.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: Aptos; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> A pathway that matches mechanism to modality—precise radiology, nurse-led safety/education, and PT-led graded conditioning—yields faster, safer diagnosis and individualized care, limiting unnecessary procedures while preserving surgical benefit for appropriate candidates.<!–EndFragment–>